2006
DOI: 10.3892/or.16.2.381
|View full text |Cite
|
Sign up to set email alerts
|

Relation between cytokine promoter gene polymorphism and toxicity of 5-fluorouracil plus cisplatin chemotherapy

Abstract: Abstract. Variability in the efficacies and toxicities of anticancer agents is a major problem. We hypothesized that polymorphisms in cytokine gene promoters may underlie genetic susceptibility to chemotherapy-induced toxicities in the Japanese. DNA was extracted from 100 patients undergoing 5-fluorouracil plus cisplatin chemotherapy. We used a caseonly design to evaluate the relation between toxicities and cytokine promoter gene polymorphisms. The following polymorphisms were genotyped: tumor necrosis factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 31 publications
0
15
0
5
Order By: Relevance
“…In the state of chronic inflammation, several cytokines could cause weight loss and malnutrition, which could result in severe side effects during chemotherapy [16, 17]. Indeed, the present study demonstrated that high CAR levels were correlated with grade 3 or 4 adverse events during AC on multivariate analysis.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In the state of chronic inflammation, several cytokines could cause weight loss and malnutrition, which could result in severe side effects during chemotherapy [16, 17]. Indeed, the present study demonstrated that high CAR levels were correlated with grade 3 or 4 adverse events during AC on multivariate analysis.…”
Section: Discussionmentioning
confidence: 53%
“…Chronic and high inflammation means hypercytokinemia that might lead to weight loss and malnutrition. Several studies reported that hypercytokinemia could produce severe side effects during chemotherapy [1316]. Furthermore, a good nutritional status slows weight loss, stabilizes body composition, and could improve quality of life in patients with advanced CRC, which reduces chemotherapy-associated side effects [17].…”
Section: Introductionmentioning
confidence: 99%
“…For several compounds [28][29][30][31][32][33][34][35][36][37][38][39], one of the polymorphic enzymes increases exposure to the toxic form of the compound and thereby induces hematotoxicity in the patient, due to higher exposure levels and not due to a specific mechanism of toxicity within the patient populations.…”
Section: Known Compounds With Hematotoxic Potentialmentioning
confidence: 99%
“…It is now clear that genetic factors influence mucositis risk in at least two ways: first, because of genetic defects, patients may have reduced levels of enzymes needed to metabolize chemotherapeutic drugs [37] ; and second, the genetic control of the pathways associated with mucositis may vary among patients [11,38,39] . In the future, pretreatment testing should assist in predicting which patients are at risk for mucositis.…”
Section: Introductionmentioning
confidence: 99%